IMPROVED FORMULA FOR FATIGUE CRACK GROWTH RATEUNDER DIFFERENT STRESS RATIO - WU QiaoGuo; CHEN XueDong; FAN ZhiChao; NIE DeFu; WEI RenChao (Jixie qiangdu)
An improved formula for fatigue crack growth rate in mode I,mode III and mixed mode I-III under different stress ratio R was proposed,which was based on J-integral range ΔJ. In the formula,the test data under different R could be normalized by correction factor M,which changed the test ΔJ under different R to ΔJeq0under R = 0,and the relationship of M and R was obtained empirically. The proposed formula was validated with available experimental fatigue crack growth data in mode I,mode III and mixed mode I-III under different stress ratio from literatures. It transpires that these test data can be well described with the present formula.